Penguatan Karakter dalam Meningkatkan Kualitas Sumber Daya Manusia Melalui Social Learning di Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan - Mutmainah, Mutmainah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Social learning is a psychological approach using observational learning theory. This model is used by the Islamic College of Syaichona Moch Cholil Bangkalan as an effort to strengthen the character to improve the quality of human resources through the programs carried out. This study aims to determine character strengthening in improving the quality of Human Resources through social learning at the Islamic College of Syaichona Moch Cholil Bangkalan. This research is a qualitative research model using a case study approach. The research scene at the Islamic College of Syaichona Moch Cholil Bangkalan (STAIS) Data collection techniques using interviews, observation, and documentation. The data analysis technique is descriptive qualitative using the Milles and Huberman models, it mains that: data reduction, data presentation, and conclusions. While the validity of the data using triangulation of methods, sources, and theories. The results of the study are: Strengthening character in improving the quality of Human Resources through social learning at the Islamic College of Syaichona Moch Cholil Bangkalan. There are two types of the Islamic College of Syaichona Moch Cholil Bangkalan. These are Firstly is programmed, and the secondly is independent, so that it is able to improve the quality of human resources with three shutters: (1) moral concept/knowledge (moral knowing), (2) Moral attitude (moral feeling), (3) behavior morals (moral behavior).